Pertanggungjawaban Pidana Terhadap Tindak Pidana Pertambangan di Wilayah Konservasi di Indonesia (Studi Kasus Kawasan Ekosistem Leuser di Aceh) - Mochamad Rizal Tsany; Hartiwiningsih; Sulistyanta (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
This study examines the issuance of a Production Operation Mining Business License (IUP) within the Kawasan Ekosistem Leuser and analyzes the potential criminal liability of public officials for granting such license. The case concerns the Decree of the Head of the Investment Coordinating Board (BKPM) No. 66/I/IUP/PMA/2017, which upgraded PT Emas Mineral Murni’s license to production operations covering 10,000 hectares, despite the environmental feasibility approval (AMDAL) only covering 3,620 hectares and part of the area being located within a legally protected conservation zone. Using a normative juridical method with statutory and case approaches, this research analyzes the decisions of the Mahkamah Agung Republik Indonesia No. 91 K/TUN/LH/2020 and No. 77 PK/TUN/LH/2021. The findings indicate serious administrative defects and the potential fulfillment of the elements of abuse of authority under Article 604 of the Criminal Code, provided that intent or gross negligence can be established, thereby demonstrating that the issuance of mining licenses in conservation areas may give rise not only to administrative annulment but also to criminal liability.